Enhanced performance of hybrid self-biased heterojunction photodetector on soft-lithographically patterned organic platform. (9th October 2018) - Chakrabarty, Poulomi; Gogurla, Narendar; Bhandaru, Nandini; Ray, Samit Kumar; Mukherjee, Rabibrata
Abstract: Nanopatterning of the active layer with feature size comparable to the wavelength of visible light is a popular strategy for improving the performance of optoelectronic devices, as these structures enhance the optical path length by light trapping due to combined contribution of multiple scattering, diffraction, and antireflection. Here, we report the fabrication of ZnO/CdS self-biased heterojunction photodetectors on soft lithographically patterned PEDOT:PSS layers with grating geometry. The present study combines the robustness of inorganic devices along with the convenience of easy patterning capability of an organic PEDOT:PSS layer. Patterns with two different line widths (L P = 350 nm, andLp  = 750 nm) have been used in this study to understand the influence of feature dimension on the device performance. We observe enhanced photoluminescence on patterned devices, in comparison to devices fabricated on flat PEDOT:PSS films, which is attributed to the increased interfacial area between the organic and inorganic layers. The spectral response [R( λ )] and specific detectivity [D  * ( λ )] are found to be higher for the devices withLp  = 350 nm as compared to other devices due to enhanced absorption within the structures due to confinement of light, which also results in reduced reflectance in devices withLp  = 350 nm.